Ewolucja technologiczna w mediach a proces zmian społeczno-kulturalnych i ich wpływ na prasę w Polsce - Marta Polaczek‑Bigaj (Ksiegarnia Akademicka Publishing, 2013)
The technological evolution of the media and the process of socio‑cultural changes and their impact on the press in Poland